1975
DOI: 10.1172/jci107945
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anemia on the ventilatory response to transient and steady-state hypoxia.

Abstract: A B S T R A C T The effects of anemia upon the ventilatory responses to transient and steady-state hypoxia were studied in unanesthetized goats. Responses to transient hypoxia (inhalation of several breaths of nitrogen) were considered to reflect peripheral chemoreceptor-mediated reflexes whereas responses to steady-state hypoxia were considered to reflect both the chemoreceptor and nonchemoreceptor influences of hypoxia upon ventilatory control. In all goats, severe anemia (hemoglobin 3.1-4.8 g/100 ml) marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Similar findings have been recorded by Lloyd and co-workers (16), who reported no ventilatory stimulation after administration of single breaths of carbon monoxide to human volunteers. We and others (8,17,18) Paintal (6) and by Mills and Edwards (7), reported increases in chemoreceptor nerve fiber discharge after inhalation of carbon monoxide. In both of these studies, however, the authors reported a time of onset of per- ipheral chemoreceptor responses of several minutes.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Similar findings have been recorded by Lloyd and co-workers (16), who reported no ventilatory stimulation after administration of single breaths of carbon monoxide to human volunteers. We and others (8,17,18) Paintal (6) and by Mills and Edwards (7), reported increases in chemoreceptor nerve fiber discharge after inhalation of carbon monoxide. In both of these studies, however, the authors reported a time of onset of per- ipheral chemoreceptor responses of several minutes.…”
Section: Discussionmentioning
confidence: 86%
“…A saturation for each period of inhalation of the test gas. The rationale and details of this method have been previously described (8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the difficulties inherent in the model (14), factors related to phlebotomy are known to influence chemoreceptor function and could affect the results obtained. These include sympathetic nervous activity (1), baroreceptor/chemoreceptor interactions (15), catecholamine effects (16), and possibly altered local blood flow (17).…”
Section: Resultsmentioning
confidence: 99%
“…A satisfactory model was more closely approximated in the study of goats with varying P50s (14). Unfortunately, the animals were made anemic, thus adding to the objections above those of iatrogenic alterations of oxygen delivery such as decreased end-capillary Po2 (18), altered cardiac output, and a possible shift towards anaerobic metabolism in low-P50 animals (19).…”
Section: Resultsmentioning
confidence: 99%